Implementing Assessment Policy: Considering the Bifactor Teachers' Satisfaction Criterion - Nordin, Mohamad Sahari; Tunku Ahmad, Tunku Badariah; Ibrahim, Mohd Burhan; Abu Libdeh, Enas Saied (Horizon Research Publishing Corporation, 2019)
The study examined teachers’ general satisfaction and specific satisfactions in implementing assessment policy. First it confirmed the validity of a four-factor teacher’s satisfaction construct. Next it identified the best-fitting measure of teacher’s satisfaction among four theoretically viable measures, namely a uni-dimension satisfaction construct, four-factor construct, second-order factor construct, and a bi-factor measure that comprised general and specifics factors. Finally, the study tested whether teachers’ agreement with the implementation of nation-wide assessment policy related to the best-fitting satisfaction model, which was the bi-factor model. A total of 2,374 teachers nested in 300 randomly selected schools in Malaysia were surveyed using a 15-item instrument. The results supported the hypotheses that the four-factor measure was adequate to explain the variability of teachers’ responses to the satisfaction items, the bi-factor model was the best-fitting model, and teachers’ endorsement of the implementation of assessment policy supported the teachers’ general satisfaction, satisfaction towards workload, and satisfaction towards pay and benefits.